The challenges of the low birth rate in China - Don Eliseo Lucero‐Prisno III; M. B. N. Kouwenhoven; Paolo Miguel Manalang Vicerra; Zheng Feei Ma; María José González Méndez; Angelica Joyce Abordo Gacutno‐Evardone; Emery Manirambona; Dawa Gyeltshen; Shuaibu Saidu Musa (Wiley, 2022)
Abstract Introduction The population growth rate of China has been steadily declining owing to the low birth rate of the country. The Chinese census also indicates that the population is also rapidly ageing because of increasing life expectancy in conjunction with the low birth rate. Method We performed a commentary to point out the challenges of the low birth rate in China. A comprehensive data search was performed in data bases such as Google Scholar and PubMed using predetermined search term. Results The decline in birth rate is due to societal changes including increasing standard of living. Although the Chinese government has recently allowed couples to have up to three children in a major policy shift, many couples remain unwilling to have more than one child due to the high cost. An increasing fraction of Chinese women, particularly among the highly‐educated urban dwellers, no longer regard marriage and parenthood as essential aspects of life. Conclusion If not addressed urgently, the declining young population will impact China's future socio‐economic situation, as there will be a smaller workforce relative to an increasing dependent older population. The repercussions may cascade to other spheres of China's status, including socioeconomic, security and global influence, if not addressed decisively. It is imperative that the country develops policies, strategies, and approaches to tackle this issue, including human capital development and the use of technology and innovations.